Association between ocular abnormalities and systemic diseases in Down Syndrome patients - Zago,Maria Isabela (2020)
Abstract Objectives: Describe ocular findings and its correlation with systemic diseases in Down Syndrome (DS) pediatric patients. Methods: Quantitative and cross-sectional study of prevalence with children aged from 0 to 25 years. Standard ophthalmic examinations performed: visual acuity, slit lamp biomicroscopy, ocular motility, static refraction and indirect ophthalmoscopy. Ocular findings were associated with comorbidities available in pediatric records of patients in FURB Down Syndrome Outpatient clinic, in which they have regular follow-up. Results: A total of 76 patients were evaluated (33 males and 43 females). Of these, 72 patients (94.73%) had ocular abnormalities. Refractive errors were the most prevalent (94.73%), followed by alterations in indirect ophthalmoscopy (40.8%), biomicroscopy (15.8%), ocular motility (15.8%) and epiphora (9.2%). From the refractive changes 13.15% had myopia; 76.31% had hypermetropia and 47.36% had astigmatism. Sytemic abnormalities were observed in 73 children. The most prevalent was thyroid diseases presented in 65.79%, followed by heart disease 61.84%, gastrointestinal disease (15.79%); abdominal hernias (14.4%); respiratory changes (14.4%); genitourinary alterations (10.53%); musculoskeletal alterations (10.53%) and epilepsy (3.95%). There was statically significant association between the presence of myopia and hypothyroidism (p = 0.01); astigmatism and heart diseases (p = 0.003); and astigmatism and genitourinary alterations (p = 0.001). Conclusion: There was a high prevalence of ophthalmologic abnormalities in this study of children with Down Syndrome. Associations between myopia and hypothyroidism, astigmatism and heart diseases, and astigmatism and genitourinary disorders were found. More studies and increase of the sample are necessary to confirm the associations of ophthalmologic abnormalities with most common systemic diseases in this population.